Gigantic macroautophagy in programmed nuclear death of Tetrahymena thermophila - Akematsu, Takahiko (Landes Bioscience, 2010)
Programmed nuclear death (PND) in Tetrahymena is a unique process during conjugation, in which only the parental macronucleus is degraded and then eliminated from the progeny cytoplasm, but other co-existing nuclei such as new micro- and macronuclei are unaffected. PND through autophagic elimination is expected to be strictly controlled, considering the significant roles in ciliates such as turnover of disused organelles and production of the next generation. Here we demonstrate that PND in Tetrahymena involves peculiar aspects of autophagy, which differ from mammalian or yeast macroautophagy. Drastic change of the parental macronucleus occurs when differentiation of new macronuclei is initiated. Combined use of monodansylcadaverine and a lysosome indicator LysoTracker Red showed that prior to nuclear condensation, the envelope of the parental macronucleus changed its nature as if it is an autophagic membrane, without the accumulation of a pre-autophagosomal structure from the cytoplasm. Subsequently, lysosomes approached only to the parental macronucleus and localized at the envelope until a final resorption stage. In addition, we found that the parental macronucleus exhibits certain sugars and phosphatidylserine on the envelope, which are possible “attack me” signals, that are not found on other types of nuclei. These findings suggest that PND is a highly elaborated process, different from the typical macroautophagy seen in other systems, and is executed through interaction between specific molecular signals on the parental macronuclear envelope and autophagic/lysosomal machineries.